Pengaruh Kepemilikan Manajerial Dan Kepemilikan Institusional Terhadap Firm Value Dengan Kebijakan Hutang Sebagai Variabel Intervening - M Rofiananda; Fefri Indra Arza; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2019)
This research was conducted to determine the effect of managerial ownership and institutional ownership on firm value with debt policy as an intervening variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. The variable value of the company is measured using price to book value by dividing the present value with the book value of the company. The sample in this study was determined by purposive sampling method. The type of data used is secondary data obtained from www.idx.co.id as well as company websites and other sites related to research. The analytical method used is Partial Last Squer Analysis.The results of this study indicate that managerial ownership has no effect on firm value, managerial ownership has a positive significant effect on firm value through debt policy, institutional ownership has a positive significant effect on firm value and institutional ownership does not affect firm value through debt policy